(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article discusses the SSPF’s design and development success with the updated controller. The aim of this SAPF was to compensate for three-phase harmonics and reactive power (3P3W). Shunt APF performance, heavily affected by DC link voltage stabilization. The DC-link voltage is reactive to load impedance changes that contribute to the system overtaking and carrying out. The DC-like voltage will experience huge conditions as charging and voltage distortions change. The PI controllers are known to regulate the DC connection voltage at their benchmark. In such situations, the optimisation of PI control gain parameter tuning can be achieved by means of an improved fuzzy logic control algorithm. In addition, PWM control techniques improves the switching action which enhances the shunt APF. The Fuzzy logic based PWM scheme is developed by MATLAB/Simulink. The controlling algorithm output is obtained by removing the current harmonics under adverse supply voltage and load conditions.